Elemen Sukses Pelaksanaan E-Government Dalam Penanggulangan Kemiskinan Di Dinas Sosial Kota Pekanbaru - Cantika, Diva; RFS, Harapan Tua (Jurnal Ilmu Administrasi Negara (JUAN), 2021)
The development of information and communication technology which is increasingly sophisticated has an impact on the advancement of electronic-based governance called e-government. The Sitanjak Makin Mantap application is a website-based application system operated by the Pekanbaru City Social Service to accelerate poverty reduction in Pekanbaru City, especially in the health, education and socio-economic fields. The Sitanjak Makin Mantap application provides easy access for the public to make complaints in this field and makes it easy for the Pekanbaru City Social Service to create a poverty database and is a step to accelerate poverty reduction in Pekanbaru City. This study aims to determine the elements of successful e-government services in poverty reduction in Pekanbaru City Social Service and factors affecting e-government services in poverty reduction in Pekanbaru City Social Service. To solve these problems, researchers used Indrajit 2010 theory about the elements of successful e-government services. The result of this research is that the operation of the Sitanjak Makin Mantap application is still not optimal, it can be seen that there are still people who do not know the existence of the application and the use of the application. Researchers conclude that there is still a lack of continuous and comprehensive socialization to the community, as well as network disruptions that have occurred at the Pekanbaru City Social Service. Therefore, researchers suggest that there is a need for consistent and comprehensive socialization and server improvements to improve network quality. Keywords: Public Service, E-government, Poverty